Self-reported and Objectively Measured Physical Activity Among a Cohort of Postpartum Women: The PIN Postpartum Study - Evenson, Kelly R. (2012)
BACKGROUND: Few studies measure physical activity objectively or at multiple time points during postpartum. We describe physical activity at 3- and 12-months postpartum among a cohort of women using both self-reported and objective measures. METHODS: In total, 181 women completed the 3-month postpartum measures, and 204 women completed the 12-month postpartum measures. Participants wore an Actigraph accelerometer for one week and completed in-home interviews that included questions on physical activity. A cohort of 80 women participated at both time points. Poisson regression models were used to determine whether physical activity differed over time for the cohort. RESULTS: For the cohort, average counts/minute were 364 at 3-months postpartum and 394 at 12-months postpartum. At both time periods for the cohort, vigorous activity averaged 1 to 3 minutes/day, and moderate activity (NHANES cutpoints) averaged 16 minutes/day. Sedentary time averaged 9.3 hours at 3-months postpartum and 8.8 hours at 12-months postpartum, out of a 19-hour day. Average counts/minute increased and sedentary behavior declined from 3- to 12-months postpartum. CONCLUSION: Interventions are needed to help women integrate more moderate to vigorous physical activity and to capitalize on the improvements in sedentary behavior that occur during postpartum.